Pathogenesis diagnosis of a pediatric patient suffering from multi-organ abscesses - Mingkun Wu; Haijuan Xiao; Yan Xiao; Tianming Chen; Xinming Wang; Xia Xiao; Ying Wang; Jianwei Wang; Lili Ren; Gang Liu (BMC, 2023)
Abstract A pediatric patient suffered from renal and hepatic abscesses (through hepatorenal space) and recovered by antibiotics and other therapies. By clinical analysis, the multi-organ abscesses might be caused by bloodstream-disseminated infection. In order to identify the pathogen, we collected kidney biopsy tissue, swabs, and plasma samples, and used metagenomics next-generation sequencing (mNGS) and some traditional methods. The results revealed that polymicrobial especially anaerobic bacteremia (Bacteroides fragilis, et al.) contributed to the abscess formation. What is more, systematic human adenovirus C (HAdV-C) infection was shown, and the virus was isolated. The titer of HAdV-2 neutralizing antibodies was 1/4 in the plasma after symptoms onset. Although the exact mechanism of HAdV-2 infection in multiple abscess formation has not been clarified, the case of multi-organ abscesses in the context of polymicrobial especially anaerobic bacteremia and HAdV infection in healthy children is infrequent.